Int J Account Res 2019
DOI: 10.35248/2472-114x.18.6.177
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Reporting: Current Trends in Financial Reporting

Abstract: Corporate financial reporting has rapidly evolved because of stakeholders' increasing demands for transparent and non-financial information. Integrated reporting (IR), which merges financial and non-financial information in reporting and promotes integrated thinking, is increasingly used to meet such demand. The objective of this article is to analyze and synthesize the existing research, examines the current trends in research, and provides some issues for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…It was also stated by Hoque [9] that stakeholders find it difficult to use the information disclosed, because it requires integrated reporting that unites the financial and non-financial measures in one report. In line with this, Joshi [11] also suggested that the company's financial reporting has grown rapidly, because it increased the stakeholders' demand for transparent and non-financial information. Cosma et al [5] also stated their findings that the stock market reacted positively to the announcement of awards, and the value was attributed by shareholders to the quality of integrated reporting.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It was also stated by Hoque [9] that stakeholders find it difficult to use the information disclosed, because it requires integrated reporting that unites the financial and non-financial measures in one report. In line with this, Joshi [11] also suggested that the company's financial reporting has grown rapidly, because it increased the stakeholders' demand for transparent and non-financial information. Cosma et al [5] also stated their findings that the stock market reacted positively to the announcement of awards, and the value was attributed by shareholders to the quality of integrated reporting.…”
Section: Resultsmentioning
confidence: 93%
“…Hoque [9] argued that many stakeholders cannot use the information disclosed because of the separation of reports, therefore the integrated reporting combines financial and non-financial measures into one report. Joshi [11] argued that the corporate financial reporting has developed rapidly due to the increasing demand of stakeholders for transparent and non-financial information. Cosma et al [5] found that the stock market reacts positively to the announcement of awards, the value attributed by shareholders to IR quality remains growing over time and very high among non-financial companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trust and reputation are crucial aspects that can affect the company's value (Deloitte, 2015). The integrated reporting process through IR requires managers to explain how the organization's strategy, governance, performance, and prospects lead to value creation in the context of its external environment in the short, medium, and long term (Joshi, 2019). The company's efforts to disclose more information through IR can be a company strategy to gain legitimacy for the policies taken, one of which is an aggressive tax avoidance policy (Dosinta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to Guidry and Patten (2012), VDT is used by firms that want to make material information readily available to investors for decision-making. Thus, management of firms usually uses VDT as a theoretical basis in minimising information asymmetry to investors and other stakeholders (Joshi, 2018). Therefore, to reduce information asymmetry, companies need to disclose non-financial information in addition to financial information to align the interest of the parties.…”
Section: Literature Reviewmentioning
confidence: 99%